برصغیر کے تفسیری ادب میں مطالعہ ادیان کی روایت: تفسیر نجوم الفرقان کا تحقیقی مطالعہ: The Tradition of Religious Studies in the Exegetical Literature of the Subcontinent: A Research Study of Tafsīr Najūm al-Furqān - Ali Raza; Dr. Muhammad Rizwan Mahmood (International Research Journal of Arabic and Islamic Studies, 2024)
Among the scriptures of Semitic religions, the Holy Qur'an holds a unique place as the unaltered word of God, serving as a source of human salvation. Its inimitability and universality elevate it to the highest rank among religious texts. To truly comprehend its message and divine guidance, one must be deeply familiar with its content. The Prophet Muhammad (peace be upon him) not only conveyed the Qur'an but also provided a detailed explanation, as mentioned in the verse: وَأَنزَلْنَا إِلَيْكَ الذِّكْرَ لِتُبَيِّنَ لِلنَّاسِ مَا نُزِّلَ إِلَيْهِمْ وَلَعَلَّهُمْ يَتَفَكَّرُونَ النحل :44 “And We sent down to you (O Muhammad) the message that you may explain clearly to the people what was sent down to them that they may reflect.” (Al-Nahl: 44) This has led to the development of Qur'anic exegesis (Tafsir al-Qur'ān), an essential field for understanding divine content. Over time, the Qur'an has been interpreted in various languages, including Urdu, where Nujum-ul-Furqān stands out as a significant contribution. Written by ‘Allama Abdul-Razzaq Bhutrālwī (b.1947), this tafsir is expected to span 22 volumes, with 11 already published, covering the Qur'an's early chapters. Bhutrālwī’s expertise in Arabic literature, jurisprudence, and Islamic philosophy shines through, making his work a valuable resource for students and scholars alike. His approach to addressing Islamic teachings, theological issues, and sectarian differences sets Nujum-ul-Furqān apart from other tafsirs. The thesis discusses this work across five chapters, covering the author's life, methodology, sources, theological points, and a comparative analysis with contemporary Urdu commentaries such as Tafhim-ul-Qur'an and Ma'arif-ul-Qur'an.